2016
DOI: 10.1016/j.jpowsour.2016.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Validation of pore network simulations of ex-situ water distributions in a gas diffusion layer of proton exchange membrane fuel cells with X-ray tomographic images

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 17329 Pore network extraction parameters were benchmarked using full morphology. Keywords:Polymer electrolyte membrane fuel cell Gas diffusion layer X-ray tomographic microscopy Pore network Full morphology Liquid water a b s t r a c t Understanding and modeling two-phase flows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 50 publications
1
48
0
Order By: Relevance
“…Although the CFM predicted capillary pressure-saturation curve for the sample used in this study is quite different from the μ-CT and literature curves, a FM model has been shown to be able to predict the capillary pressuresaturation curve for SGL 24BA. 62 Therefore, analysis of different samples might be needed to improve the limitations of the CFM model. Schulz et al 53 proposed an improvement to the FM model by creating fictitious spheres with diameters increased by the cosine of the contact angle to account for the wettability of the walls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CFM predicted capillary pressure-saturation curve for the sample used in this study is quite different from the μ-CT and literature curves, a FM model has been shown to be able to predict the capillary pressuresaturation curve for SGL 24BA. 62 Therefore, analysis of different samples might be needed to improve the limitations of the CFM model. Schulz et al 53 proposed an improvement to the FM model by creating fictitious spheres with diameters increased by the cosine of the contact angle to account for the wettability of the walls.…”
Section: Resultsmentioning
confidence: 99%
“…Vogel et al 60 and Kim et al 61 however did not study fibrous media, such as gas diffusion electrodes. Agaesse et al 62 used μ-CT reconstructions of partially saturated GDLs at different capillary pressures to validate numerically simulated liquid water distributions using a pore network model and a full morphology approach. Their work demonstrated the capability of the numerical models to predict capillary pressure-saturation curves and saturation profiles similar to those obtained from the μ-CT reconstructions.…”
Section: F554mentioning
confidence: 99%
“…The median filter is actually recommended when preserving edges is desired, which is not the case here. Agaesse et al [35] applied a gray-scale reconstruction, sometimes referred to as an H-minima filter, that converts peaks to plateaus to remove small local peaks [44]. As discussed below, however, plateaus are also problematic and should be avoided.…”
Section: Preparing Imagementioning
confidence: 99%
“…Rounding out the methods is the watershed segmentation of the pore space, that was originally investigated by Thompson et al. [32] and Sheppard et al [33] over a decade ago, but has received surprisingly little attention until recently [34,35]. The common thread running through the existing network extraction algorithms is that they are essentially optimized for rock and soil, due to the importance of these media in oil recovery and aquifer management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation